IMPACT OF DIESEL FUEL GENERATORS ON SOIL HEAVY METALS (Journal of Engineering Studies and Research, 2023)
Heavy metals are ubiquitous and are released into the atmosphere/ environment by a variety of natural processes, but their quantities have been greatly augmented by anthropogenic activities. This study investigated the concentration of heavy metals Iron (Fe), Arsenic (As), Cadmium (Cd), Chromium (Cr), Zinc (Zn), Manganese (Mn) and Lead (Pb) in the soil around the power plant obtained at the old power plant, new power plant and a far-away point from the plants which served as the control. In each location, two samples were obtained top layer and bottom layer of soil. Standard laboratory methods were employed for all the analyses. High concentration was obtained for the selected heavy metals in the soil at both the old and the new power plants with Arsenic having an average of 0.67 mg/kg and 0.40 mg/kg, Lead having an average of 2.63 mg/kg and 1.67 mg/kg, Iron having 1.25 mg/kg and 0.95 mg/kg, Chromium having 1.08 mg/kg and 0.67 mg/kg, Cadmium having 1.46 mg/kg and 0.54 mg/kg, Manganese having 1.97 mg/kg and 1.86 mg/kg and Zinc having 2.43 mg/kg and 0.86 mg/kg at the old and new site respectively. All the obtained concentration levels are above the permissible limit of the United States, United Kingdom, Europe and WHO. It is expedient that necessary measures be put in place to control the emissions from the plants to reduce the contaminating impact of the soil around the power plant as well as moving some human intakes far from the locations.
Keywords: impact, heavy metals, soil, environment, diesel fuel